2018
DOI: 10.1002/ccd.27907
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia after transcatheter aortic valve implantation. A comparison between balloon‐expandable and self‐expanding valves

Abstract: Background Thrombocytopenia after transcatheter aortic valve implantation (TAVI) is common and has been related to higher mortality and major complications. No comparison between balloon‐expandable (BEV) and self‐expanding valves (SEV) regarding drop platelet count (DPC) has been reported to date. The objectives of this study were to analyze the differences in DPC between BEVs or SEVs and their prognostic implications in clinical outcomes. Methods We retrospectively analyzed patients undergoing TAVI. Platelet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 28 publications
(68 reference statements)
5
36
0
1
Order By: Relevance
“…This result is consistent with previous studies. 5,6 These studies revealed that differences in TAVI valves affected DPC severity. However, the nadir platelet count was not considered in those studies.…”
Section: Transcatheter Aortic Valve Selectionmentioning
confidence: 96%
See 2 more Smart Citations
“…This result is consistent with previous studies. 5,6 These studies revealed that differences in TAVI valves affected DPC severity. However, the nadir platelet count was not considered in those studies.…”
Section: Transcatheter Aortic Valve Selectionmentioning
confidence: 96%
“…Only a few studies have been reported in which the use of balloon-expandable valves was associated with a greater decrease in post-procedural platelet count than the use of self-expanding valves. 5,6 The purpose of the present study was to investigate the frequency of TAVI-related thrombocytopenia and its predictors, especially with regard to the procedural access site and TAVI device selected. The mid-term clinical impact of TAVI-related thrombocytopenia was also examined.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[59][60][61][62][63][64] Finally, a periprocedural thrombo-inflammatory state and reduced platelet turnover in the older patient may act synergistically, resulting in transient thrombocytopenia in 69-87% of TAVI patients, signalling severe impairment of general homeostasis. [65][66][67] Gastrointestinal bleeding associated with aortic stenosis is due to the shear stress and flow turbulence across the stenotic aortic valve, which may cause the cleavage of high-molecular-weight multimers of von Willebrand factor, a coagulation protein responsible for haemostasis.…”
Section: Bleeding Eventsmentioning
confidence: 99%
“…Transcatheter aortic valve implantation (TAVI) is used to treat high-risk patients with severe aortic stenosis [1][2][3]. However, TAVI-related thrombocytopenia is common [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], with platelet counts decreasing to < 100 × 10 3 /µL in more than one-third of patients who undergo TAVI [4,5]. Previous studies have shown that the nadir platelet count is approximately 50-60% of the baseline value, occurs on postoperative day 2-3, and begins to recover after postoperative day 5 [4,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%